Clinical significance of Cyclin D1 by complete quantification detection in mantle cell lymphoma: positive indicator in prognosis - Yan Yang; Liling Song; Ying Yin; Yuan Gao; Yunjun Wang; Shishou Wu; Jun Wang; Yu Pan; Xiaolong Sui; Lei Jiang; Yunyun Zhang; Guohua Yu (BMC, 2024)
Abstract Objectives The positive expression of Cyclin D1 in immunohistochemical (IHC) staining serves as the cornerstone for diagnosing mantle cell lymphoma (MCL). However, existing literature does not conclusively establish whether the expression ratio and staining intensity significantly influence diagnostic outcomes or patient prognosis. In this retrospective study, the correlation between comprehensive Cyclin D1 quantification and the prognosis of MCL patients was studied. Methods The Cyclin D1 protein level was assessed in 120 formalin-fixed paraffin-embedded samples from MCL patients using the quantitative dot blot (QDB) analysis technique. R language software was employed for statistical analysis to determine the optimal threshold with statistical significance. Additionally, Kaplan-Meier method was utilized to evaluate the relationship between the absolute level of Cyclin D1 protein and overall survival (OS) of patients. Furthermore, the Chi-square test was applied to analyze the causes of single and multiple fractures, with a significance level of p < 0.05. Finally, the Log-rank test was used to compare two survival curves, where a significance level of p < 0.05 was considered statistically significant. Results At the optimized cutoff of 0.46 nmol/g, univariate analysis revealed a positive correlation between Cyclin D1 protein level and patient survival (OS). Specifically, in the subgroup with complete quantification of Cyclin D1 higher than the cutoff, the 5-year OS was 18%, whereas in the subgroup with complete quantification of Cyclin D1 lower than the cutoff, the 5-year OS was 4.8% (Log-rank test, P = 0.017). This indicates that patients with Cyclin D1 levels above the cutoff had significantly better overall survival compared to those below the cutoff. Additionally, in the Pearson distribution test, Ki-67 emerged as an independent prognostic factor for the complete quantification of Cyclin D1. Notably, Cyclin D1 complete quantification results remained unaffected by factors such as gender, age, LDH (Lactate Dehydrogenase) level, Ann Arbor stage(AAS), Ki-67, IPI(International prognostic index), MIPI(Mantle International prognostic index), and MIPI-c (MIPI Combined with Ki-67 Proliferation Index Chi-square test, p > 0.05). Conclusions Comprehensive Cyclin D1 quantification, especially above a threshold, significantly correlates with better overall survival in MCL. This highlights its prognostic importance in MCL management. Full quantification of CyclinD1 aids MCL prognosis, while QDB technology for biomarker quantification supports precise clinical prognostic stratification.